18. CLINICAL IMPACT OF OCCULT HEPATITIS B VIRUS INFECTION: A CASE SERIES (Vietnam Journal of Community Medicine, 2025)
The Taormina Consensus Conference (Italy, 2008 and 2018) defined occult hepatitis B virus infection (OBI) as the presence of hepatitis B virus DNA in the hepatocytes or serum of individuals who had tested negative for serum HBV surface antigen with currently available assays. OBI can lead to viral reactivation; liver fibrosis and hepatocellular carcinoma (HCC). The diagnosis is also easy to overlook, as the negative HBsAg in such cases can be falsely reassuring. This case series describes three patients (1 male and 2 females, mean age 58) who were diagnosed with OBI at Ho Chi Minh City MEDIC Medical Center between 2021 and 2024. These patients had variable clinical presentations and outcomes. This case series illustrates the clinical significance of OBI and the importance of screening for OBI in HBsAg negative patients with signs of chronic or severe hepatic inflammation.
Keywords: occult hepatitis B virus infection; OBI; liver fibrosis; hepatocellular carcinoma